Ginger Alleviates DSS-Induced Ulcerative Colitis Severity by Improving the Diversity and Function of Gut Microbiota - Guo, Shanshan; Geng, Wenye; Chen, Shan; Wang, Li; Rong, Xuli; Wang, Shuocun; Wang, Tingfang; Xiong, Liyan; Huang, Jinghua; Pang, Xiaobin; Lu, Yiming (Frontiers in Pharmacology, 2021)
The effects of ginger on gastrointestinal disorders such as ulcerative colitis (UC) have been widely investigated using experimental models; however, the mechanisms underlying its therapeutic actions are still unknown. In this study, we investigated the correlation between the therapeutic effects of ginger and the regulation of gut microbiota. We used dextran sulfate sodium (DSS) to induce colitis and found that ginger alleviated the pathological changes of colitis and decreased the mRNA expression levels of interleukin-6 and inducible nitric oxide synthase in mice. 16s rRNA sequencing analysis of the feces samples showed that colitis mice had an imbalance of intestinal flora with lower species diversity and richness. At the phylum level, higher abundance of Pathogenic bacteria Proteobacteria and firmicutes were observed; and at genus level, most samples in model group showed an increase in Lachnospiraceae_NK4A136_group. Overall analysis illustrated the increase in the relative abundance of Lactobacillus_murinus, Lachnospiraceae_bacterium_615, and Ruminiclostridium_sp._KB18. These increase pathogenic bacteria that showed in the model mice were decreased when treated with ginger. DSS treated mice showed a lower abundance of Muribaculaceae in colitis mice, and ginger adjusted this disorder. The bacterial community structure of the ginger group that analyzed with Alpha index and Beta index was more similar to the control group. The results also illustrated that the altered intestinal microbiomes affected physiological functions and adjusted key metabolic pathways in mice. In conclusion, this research presented that ginger reduced DSS-induced colitis severity and had positive effect of regulating intestinal microbiome. Based on the series of data in this study, we hypothesis that ginger can improve diseases by restoring the diversity and functions of gut microbiota.